2022
DOI: 10.1039/d2ee00571a
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole additives in 2D halide perovskites: impacts of –CN versus –CH3 substituents reveal the mediation of crystal growth by phase buffering

Abstract: The unique sandwiched structure and favorable crystallization kinetics have endowed two-dimensional (2D) halide perovskites with excellent ambient stability and facile film formation compared to their three-dimensional counterparts. However, the heterogeneous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 35 publications
1
44
0
1
Order By: Relevance
“…The radial integral intensity plot along the (110) diffraction ring (the q was around 10 nm –1 ) as a function of the azimuth angle of the five perovskite films is given in Figure e,f. ,, As shown in Figure S1, the perovskite films show a preferential orientation at azimuth angles of 90.5° for (110) planes (Figure e), demonstrating that the Col-QDs did not affect the preferential (111) orientation and crystallization of the perovskite layer . As shown in Figure S2, the smaller FWHM of the (111) orientation for the 2D perovskite film with 1 mg/mL Col-QD addition concentration indicates that the Col-QDs can improve the vertical stacking of the 2D perovskite arrays, which helps to enhance the transport of carries from the perovskite bulk to the electron transport layer (ETL) and hole transport layers (HTL). , …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The radial integral intensity plot along the (110) diffraction ring (the q was around 10 nm –1 ) as a function of the azimuth angle of the five perovskite films is given in Figure e,f. ,, As shown in Figure S1, the perovskite films show a preferential orientation at azimuth angles of 90.5° for (110) planes (Figure e), demonstrating that the Col-QDs did not affect the preferential (111) orientation and crystallization of the perovskite layer . As shown in Figure S2, the smaller FWHM of the (111) orientation for the 2D perovskite film with 1 mg/mL Col-QD addition concentration indicates that the Col-QDs can improve the vertical stacking of the 2D perovskite arrays, which helps to enhance the transport of carries from the perovskite bulk to the electron transport layer (ETL) and hole transport layers (HTL). , …”
Section: Resultsmentioning
confidence: 93%
“…31 As shown in Figure S2, the smaller FWHM of the (111) orientation for the 2D perovskite film with 1 mg/mL Col-QD addition concentration indicates that the Col-QDs can improve the vertical stacking of the 2D perovskite arrays, which helps to enhance the transport of carries from the perovskite bulk to the electron transport layer (ETL) and hole transport layers (HTL). 41,42 The devices' corresponding J−V characteristics with the different additions are shown in Figure 5a. The best Col-QD addition concentration was 1 mg/mL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Antiferroelectric or ferroelectric materials have been always regarded as a promising candidate for electronic energy storage devices, owing to their natural double polarization versus electric field (P−E) hysteresis loops. Recently, the two-dimensional (2D) organic and inorganic hybrid perovskite materials, with structural diversity and tunability, have received a large number of attracted interests [18,25,26]. For example, Wu et al have reported a new type of 2D Ruddlesden−Popper (RP) hybrid perovskite antiferroelectric, ((CH 3 ) 2 CH 2 NH 3 )2CsPb 2 Br 7 showing an above-room-temperature Curie temperature at 353 K, and trigging by the synergistic dynamic motion of inorganic Cs atoms and organic isobutyl ammonium cations [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that organic-inorganic hybrid perovskite materials exhibit excellent properties and ultra-high sensitivity in piezoelectric effect studies, and the preparation of materials does not require expensive equipment and processes. However, a series of problems in organic-inorganic hybrid perovskite materials, such as the humidity and thermal stability of the material [24][25][26], seriously restrict their industrialization development and application. Therefore, methods to obtain cheap and stable perovskite materials are of great significance for the widespread development of ultrasonic sensors in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation